Influence of Vibrations on the Rheological Properties of Drilling Fluids and Its Consequence an Solids Control - Saasen Arild; Hodne Helge (Applied Rheology, 2016)
Removing drilled cuttings from the drilling fluid flowing out of an oilwell is essential for obtaining good drilling conditions. Currently this solids control process is performed by use of shale shakers and vacuum devices. Throughout the last decades, the design and performance of the primary solid control devices have changed significantly. Flow through screens is strongly dependent on the rheological properties of the drilling fluid. Drilling fluids with high extensional viscosity seldom have a very strong gel structure, and are generally not affected equally much by vibrations. This explains why solids control is more difficult using a KCl/polymer water based drilling fluid than using an oil based drilling fluid. This article focuses on describing how the drilling fluid viscous properties alter when being exposed to vibrations like those on primary solids control devices. It is based on theoretical analysis, and rheological studies in the laboratory. The solids control efficiency resulting from using different screen configurations is outside the scope of this article, as this topic requires a higher focus on separation technology.